Model discrimination by reaction dynamics of steam reforming of methanol with CO formation - Lwin, Ye; Yusuf, Suzana; Subbarao, D. (2009)
Comparative simulation studies of the kinetics of steam reforming of methanol were carried out at 473-573 K and steam/methanol molar feed ratio (1-1.4) using the recently proposed and widely accepted rate models including CO formation. The models considered were the Peppley model, which is based on the reforming-decomposition-shift mechanism, and the Lee model, which is based on the reforming-reverse WGS reaction scheme. Both models simulated consistent profiles of concentration in the reactor. However, the Peppley model simulated essentially negative extent of WGS reaction at high temperatures, in consistence with the predicted local thermodynamics that showed high potential for reverse water-gas shift (RWGS) reaction. On the other hand, Lee model simulated positive and highly oscillating intrinsic kinetics of the RWGS reaction for all conditions, violating the predicted local thermodynamics that showed no potential for RWGS reaction.